Harnessing Islamic FinTech for disaster risk financing: Innovative strategies for economic resilience and sustainable development - Nipa, Nazmin Naher; Zahid, Zahiduzzaman; Amin, Md. Ruhul; Alamm, Md. Shahed; Haque, Zubair Muhammad Ehsanul; Parves, Muhammad Masud (Journal of Islamic Economics Lariba, 2026)
IntroductionNatural and human-induced disasters have become more frequent and severe, resulting in significant economic losses, particularly in developing countries. Traditional disaster risk financing mechanisms often fail to adequately serve vulnerable populations due to high costs, limited accessibility, and delayed disbursements. This study explores how Islamic finance principles, when integrated with financial technology (FinTech), can provide scalable, Sharia-compliant solutions for enhancing disaster risk financing (DRF).ObjectivesThe primary objective of this research is to examine the potential of combining Islamic finance mechanisms such as Zakat, Sadaqah, and Waqf with FinTech innovations, including blockchain, smart contracts, and mobile platforms, to improve accessibility, efficiency, and transparency in DRF. This study aims to identify how these integrated solutions can enhance economic resilience, financial inclusion, and alignment with the United Nations Sustainable Development Goals (SDGs).MethodA mixed-methods approach was employed, utilizing case studies from Southeast Asia, the Middle East, and Africa, alongside a survey (n=100) and expert interviews (n=12). The case studies focused on the application of Islamic finance and FinTech innovations in disaster-prone regions. Surveys and interviews provided empirical insights into the effectiveness of these solutions and the challenges faced in implementing them.ResultsThe study found that Islamic FinTech platforms raised an average of $24 million per disaster event, reduced disbursement times by 30-40%, and achieved adoption rates of 45-70%. Despite challenges such as regulatory barriers and digital literacy gaps, these solutions significantly enhanced financial inclusion and economic resilience, aligning with SDG 1, SDG 9, and SDG 13.ImplicationsThe research suggests that integrating Islamic finance with FinTech can provide a transformative approach to DRF, offering more inclusive, efficient, and transparent solutions. Policy recommendations include the development of unified Sharia-compliant FinTech standards and infrastructure investments to scale these solutions in disaster-prone regions.Originality/NoveltyThis study contributes to the emerging field of Islamic FinTech by bridging the gap between Islamic finance principles and modern digital technologies to enhance disaster risk financing, particularly in developing and Muslim-majority countries.